2019
DOI: 10.1109/jphot.2019.2923195
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Polysilicon Antenna for Terahertz Detection

Abstract: Resonant antennas have garnered considerable interest in terahertz and visible regimes owing to its extraordinary localized field concentration capability. In this work, we experimentally demonstrate a novel metal-free terahertz detector, which is fashioned by heavily doped polysilicon using standard CMOS process. The computational results show that the incident field can be largely enhanced within the antenna gap area at the resonance of 650 GHz. The room temperature measured results show that the responsivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In another report, a heavily doped resonant polysilicon antenna was proposed as a THz detector. Thus, the antenna cross-sectional area is chosen as the effective detection area where a strongly confined field is transferred to a FET detector [127]. It should be noted that the normalization of the incident THz radiation based on the physical sub-wavelength detector area would yield a higher responsivity value, due to the assumption that the THz power is focused into a such small area.…”
Section: 𝐴 =mentioning
confidence: 99%
“…In another report, a heavily doped resonant polysilicon antenna was proposed as a THz detector. Thus, the antenna cross-sectional area is chosen as the effective detection area where a strongly confined field is transferred to a FET detector [127]. It should be noted that the normalization of the incident THz radiation based on the physical sub-wavelength detector area would yield a higher responsivity value, due to the assumption that the THz power is focused into a such small area.…”
Section: 𝐴 =mentioning
confidence: 99%
“…SPR antenna [17], [18] has a strong local field concentration capability at terahertz frequency, the mechanism of which can be explained by the collective oscillations of the resonant electrons in the radiating part of the antenna [19]. In previous studies, we have demonstrated the feasibility of the polysilicon-based SPR antenna for CMOS THz wave detectors [20], [21]. For such a THz detector, the size of pixels is about several micrometers.…”
Section: Introductionmentioning
confidence: 99%